An Opsonizing Monoclonal Antibody That Recognizes a Noncapsular Epitope Expressed on Cryptococcus neoformans - Merkel, Glenn J. (American Society for Microbiology, 1999)
A mouse hybridoma secreting a monoclonal antibody (MAb) that bound a noncapsular epitope expressed on C. neoformans was developed by immunizing BALB/c mice with formalin-killed serotype A yeasts. The hybridoma, designated CSFi, secreted an immunoglobulin G2b MAb that reacted with all C. neoformans serotypes tested, including the acapsular mutant ATCC 52817 (Cap67). Postsectioned immune electron microscopy revealed extensive binding of the MAb to the cell walls of both encapsulated and acapsular yeasts. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot analysis of secreted antigens recovered from concentrated culture supernatants from both encapsulated and acapsular strains was conducted. The results showed that this MAb bound predominantly to antigens with molecular masses of approximately 75 and 100 kDa. A competitive enzyme-linked immunosorbent assay was used to demonstrate that the MAb was not cross-reactive with purified glucuronoxylomannan derived from either serotypes A or D. Experiments conducted with mouse peritoneal phagocytes and the mouse phagocyte-like cell line, J774A.1, demonstrated that the CSFi MAb opsonized the yeasts and increased their adherence to both types of phagocytic cells. We conclude, therefore, that antibodies directed at noncapsular epitopes can serve as opsonins and may have a role in modulating cryptococcal infection.